METHOD OF GRAMMATICAL STRUCTURE FORMALIZATION OF A NATURAL LANGUAGE - Badyorina, Lyubov (Proceedings of National Aviation University (archive), 2013)
The paper considers the application of mathematical tools for formalizing of grammatical structures to facilitate the Phrases processing by computer means.